2017
DOI: 10.21608/asejaiqjsae.2017.4102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kaolin Sprays on Fruit Quality and Storability of Balady Mandarin

Abstract: The present work was conducted in a private orchard situated at Motobus, Kafr El-Sheikh governorate, Egypt during 2014-2015 and 2015-2016 seasons. The main objective of this study is to evaluate the effect of kaolin foliar applications on disorder fruits, yield, fruit quality and storability of Balady mandarin fruits (Citrus reticulate,B) for 45 days. Trees were sprayed with kaolin at five concentrations (0, 1, 2, 3 and 4% ) for three times in summer. Fruit samples were divided into two groups and stored at 2±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(11 reference statements)
4
3
0
Order By: Relevance
“…Anyhow, these results are in agreement with those obtained by Kerns and Wright, (2000) ;Glenn, (2009); Colavita et al, (2011); Alvarez et al, (2015) and Zaghloul et al, (2017). Effect of kaolin, screen duo sprayed once or twice on number of sunburned fruits per tree, sunburned fruits weight and sunburned fruit weight /weight of yield (%) of Keitt mango fruits.…”
Section: Results Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Anyhow, these results are in agreement with those obtained by Kerns and Wright, (2000) ;Glenn, (2009); Colavita et al, (2011); Alvarez et al, (2015) and Zaghloul et al, (2017). Effect of kaolin, screen duo sprayed once or twice on number of sunburned fruits per tree, sunburned fruits weight and sunburned fruit weight /weight of yield (%) of Keitt mango fruits.…”
Section: Results Discussionsupporting
confidence: 91%
“…The obtained results are in harmony with those attained by Glenn et al, (2002); Jifon and Syvertsen, (2003); Gindaba and Wand, (2005);Wand et al, (2006); Colavita, (2011); EL-Gioushy et al, (2017); Ennab et al (2017); and Zaghloul et al, (2017). Effect of Kaolin, screen duo sprayed once or twice on some fruit quality properties of Keitt mango fruits.…”
Section: Results Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As per the study, the percentage of fruit drop other than sunburned fruits per tree decreased with increased concentration of antitranspirants rate resulting in treatment T7 (GA3 15 ppm + Urea 1% + Kaolin 5%) might be due to the GA3 minimizes fruit drop and increased in fruit retention and kaolin appears to be an important and helpful tool to reduced insect attack and pest diseases of fruit damage also could be a valid alternative to intensive application of insecticide. Similar results found by Mohsen and Asharaf (2019) in grapes, Kumar et al (1975) [29] in sweet lime and Ennab et al (2017) [65] in balady mandarin. From table no 2 the maximum reduction percentage of sunburned fruits (62.61%) was noted in treatment T7 (GA3 15 ppm+ urea 1%+ kaolin 5%) followed by T9 (61.07%) whereas, minimum reduction percentage was observed in T10 (Control).…”
Section: Results and Discussion Effect Of Chemical Substances On Sunbsupporting
confidence: 87%
“…Kaolin, the second Biostimulant used in this experiment is a natural mineral with the formula Al2Si2O5 (OH)4, and found in Egypt and used as a foliar spray on fruit trees to protect them against abiotic stresses like extreme environmental conditions, (temperate light, and deficiencies in nutrition). Zaghloul et al, (2017) specified that spraying kaolin at 4%, three times in summer months, on mandarin trees, was effective in reducing fruit pre-harvest disorders and improving yield and fruit quality at harvest, in addition to increasing storage time of mandarin compared to control. In another experiment by (Eldeen et al, 2015), it was concluded that treatments of spraying kaolin, young mango trees gave a high effect on improved growth parameters of these trees.…”
Section: Introductionmentioning
confidence: 99%